Sustainability of vegetable farming in Southern Mindanao, Philippines I. impact of vegetable farming on soil properties - Rasco, E.T., Jr (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2005)
A case study and survey were conducted in 2001-2002 in Kapatagan, a mid-elevation vegetable production area in Digos City, Southern Mindanao, Philippines to determine the impact of vegetable farming on soil properties. The case study of 27 farms with different lengths of cultivation (less than 10 yr, 11-20 yr and more than 20 yr) and operated by farmers with different levels of success, showed that all had highly acidic soils and magnesium (Mg) levels that were medium to low. More than 60% of the farms had inadequate levels of organic matter (OM), phosphorus (P) and zinc (Zn), and low cation exchange capacity (CEC). More than 0% of the farms exceeded the threshold level for bacterial wilt, likely because of the use of infected seed in potato cultivation. OM, pH, CEC and soil bacterial count were significantly and negatively correlated with years under cultivation. A separate study done in 2004 showed that 100% of 33 farms sampled were deficient in boron (B). Among the various soil parameters, OM was the only one that was found to be positively and significantly correlated with success in farming. The survey involving 209 respondents revealed that farmers coped with soil deterioration by applying excessive chemical NPK fertilizers, a practice which probably caused and generally aggravated the problem. The studies suggest that farmers generally need to apply dolomitic lime, OM and micronutrients (particularly B), coupled with judicious applications of chemical NPK and a sound bacterial wilt management program.